Coliform AND Escherichia coli TESTS IN THE AIR OF THE WELLS OF THE VILLAGE SIDO MAKMUR KUALA DISTRICT LANGKAT DISTRICT - Mhd Yusuf Nasution; Hudson Sidabutar; Wulandari Wulandari; Ahmad Shafwan S Pulungan (JBIO: jurnal biosains (the journal of biosciences), 2022)
Dug well water is a source of clean water that is used by 99.39% of the residents of Sido Makmur Village, Kuala District, Langkat District to meet their daily needs. The majority of people who have cow pens around dug wells trigger the importance of conducting microbiological water quality research, given the existence of dug wells that are very vulnerable to cow manure contamination. Therefore the research sample was taken based on the distance of the dug well with a cattle pen that is less than 5 meters. Five samples from Inpres Hamlet, Petak Dua Hamlet, Handayani Hamlet, Sidorejo Hamlet and Mandailing Hamlet were tested using the Most Probable Number (MPN) method in the North Sumatra Province Health Laboratory, to determine the presence of Coliform and Escherichia coli through the estimation test, assertion test , and test the completeness and coloring of grams. Then a biochemical reaction test is performed to confirm the presence of Escherichia coli. The results showed that all dug well water samples with sample codes ASG 01, ASG 02, ASG 03, ASG 04 and ASG 05 were positively polluted by Coliform through assertion tests with total Coliform exceeding the 80% threshold and below the threshold of 20% based on Minister of Health Regulation No. 416 / MENKES / PER / IX / 1990 concerning Requirements and Supervision of Water Quality. Then there is also the content of Escherichia coli in the five samples which exceeds the established threshold, the positive results of E.coli have also been strengthened through the results of gram staining and biochemical reaction tests. Therefore the dug well water samples tested are not feasible or do not meet the microbiological quality requirements for clean water.